The Distribution Characteristics and Genesis Analysis of Overpressure in the Qiongzhusi Formation in the Zizhong Area, Sichuan Basin - Xuewen Shi; Yuran Yang; Qiuzi Wu; Yanyou Li; Yifan He; He Tian; Zhenxue Jiang; Zhongyu Bi; Huan Miao (Applied Sciences)
Accurately predicting the genesis and distribution of reservoir pressure is essential for comprehending the distribution of oil and gas reservoirs while mitigating drilling risks. In the Qiongzhusi Formation of the Sichuan Basin, overpressure has developed, leading to high production levels in several wells. However, the distribution and causal mechanism of overpressure within the Qiongzhusi Formation remain unclear at present. This study utilizes logging data from representative drilling wells to identify the causes of overpressure in the Qiongzhusi Formation and predict the characteristics of pressure distribution. The results indicate that the pressure coefficient of the Qiongzhusi Formation ranges from 1.01 to 2.05 and increases with burial depth. The overpressure in the Qiongzhusi Formation is attributed to fluid expansion, disequilibrium compaction, and pressure transmission. The contribution of disequilibrium compaction to pressure is 9.44 MPa, while hydrocarbon generation from organic matter contributes 82.66 MPa, and pressure transmission contributes 37.98 MPa. Additionally, the uplift erosion unloading effect and geothermal decline result in pressure reductions of approximately 26.68 MPa and 56.56 MPa, respectively. This study systematically elucidates the causes and distribution of overpressure in the Qiongzhusi Formation, providing valuable insights for subsequent exploration and development of shale gas in this formation.